DEVELOPMENT OF A LEARNING MODEL BASED ON THE QUIZIZ APPLICATION AS AN EFFORT TO DEVELOP LITERATURE LEARNING - Aditya Permana; Mimin Sahmini; Fauzi Abdilah; Senny Shaika (STKIP Siliwangi, 2024)
The development of learning models is urgent to be researched and studied continuously. This is done for effectiveness in achieving maximum learning goals. Apart from that, interests and talents in studying literature need to be developed. In fact, studying literature can develop students' character so that it is relevant to the educational goals in the independent curriculum. The aim of this research is to develop a learning model based on the Quizizz application as a medium for developing literary learning. The method used in this research is R&D with 4D from Thiagharajan. Researchers developed a learning model in four stages, including: 1) define, 2) design, 3) development, 4) disseminate. The results of this research are to provide information on the use of Quizizz and an overview of using features in the Quizizz application that can be used in literature learning, describe a questionnaire related to the effect of using Quizizz on motivation in learning, and explain the results of tests in the form of quizzes on increasing student competence in literature learning. Learning literature using the Quizizz application is very effective and adds color to learning, so that learning becomes fun and makes students active so that learning objectives are achieved optimally.